MEMBANGUN KEPEDULIAN MAHASISWA UNTUK MEWUJUDKAN LINGKUNGAN KAMPUS YANG BERSIH DAN SEHAT - Cilda Thesisa Ilmawan Dzinnur; Mohammad Setya Pandu (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity is motivated by increasing environmental degradation caused by disasters such as flooding, deforestation, and pollution. Creating a clean and healthy campus environment at Sunan Giri University of Surabaya is an important effort to improve the quality of life of students and the academic community. This activity aimed to promote environmental awareness and encourage the maintenance of a clean and healthy campus, initiated through a morning assembly to communicate program objectives. The activity employed the Participatory Action Research (PAR) method and was conducted within the campus environment. The results show that students developed greater awareness of the importance of campus cleanliness and environmental health. Overall, students demonstrated a high level of concern for environmental sustainability. This activity contributes to increasing students’ awareness, creating a clean and comfortable campus environment, and fostering social responsibility toward the environment.